Implementasi Permainan Edukasi dalam Meningkatkan Kedisiplinan Anak-Anak di Panti Asuhan - Muhidin Nasir; Urwatil Wusqo; Ali Akbar Hidayat; Muhamad Bai'ul Hak; Muhammad Dzul Fadlli (Yayasan Literasi Sains Indonesia, 2023)
One of the problems faced by the younger generation today is the problem of discipline. The discipline attitude of children is still far from ideal, such as they do not care about waste, put the clothes in bad ways, often getting up late in the morning, and other problems. Discipline problems occur in almost all parenting conditions. Discipline problems occur in direct parenting by parents, also occur in day care, including in orphanage care. Based on these problems, we want to be actively involved in growing the discipline of children, especially in orphanages. We carry out an educational implementation pattern to develop the discipline attitude of the orphanage children. The method of playing while learning will make children more enthusiastic about participating in the learning process. Playing while learning activities also have the virtue of increasing children's interest as a first step in improving discipline. The stages in this service go through three stages, namely pre-service in the form of observations and interviews related to the problems that occur. The second stage is the implementation of community service in the form of counseling and the implementation of educational games that can improve children's discipline. Furthermore, the third stage is post-service by evaluating the level of discipline of the orphanage children. Based on the activities carried out at the orphanage, the children took part in the program well. As for the results of periodic evaluations conducted, educational activities in improving children's discipline are starting to show positive developments. This is reflected in the attitude of the orphanage children who have started caring to waste, put the clothes in the right place, and getting up early.